Stages and Main Tasks of the Century-Long Control Theory and System Identification Development. Part VI. Model Predictive Control - Gubarev, V.; Romanenko, V. (Проблеми керування та інформатики, 2024)
This paper examines one of the relatively new directions in the field of control theory and practice, known as model predictive control. The ideas behind it, its connection with optimal control theory, and numerical methods for solving optimization problems are described. An example of cognitive modeling of evolutionary demographic processes in Ukraine and the possibility of controlling them using a predictive model when the model contains unstable eigenvalues is considered. To solve predictive control problems, it is proposed to use trajectory models directly derived from the Cauchy formula, especially for discrete systems, instead of local descriptions in the state space. Розглядається один з відносно нових напрямів у галузі теорії та практики керування, що отримав назву керування за моделлю передбачення. Описуються ідеї, покладені в його основу, зв’язок з теорією оптимального керування та чисельними методами розв’язання задач оптимізації. Розглянуто приклад когнітивного моделювання еволюційних демографічних процесів в Україні та можливості керування ними за прогнозною моделлю, коли модель містить нестійкі власні значення. Запропоновано під час вирішення задач прогнозного керування замість локального опису у просторі станів використовувати траєкторні моделі, які безпосередньо випливають з формули Коші, зокрема для дискретних систем.